Evaluación de las estrategias de aprendizaje en estudiantes de odontología y su relación con el rendimiento académico (2021)
Objective: To evaluate learning strategies and their relationship with academic performance in dental students. Materials and methods: A descriptive observational study was carried out with 268 active students in the second period of 2019 of the dentistry program, the CEVEAPEU questionnaire by Gallardo, Suarez and Pérez (2009) was applied. The academic average of the students' grade system was recorded, participation was voluntary